Trends and problems of e-commerce development in the Republic of Kazakhstan - Zhumadilova, M.A.; Issayeva, A.Zh.; Aitimov, B.Zh. (Bulletin of the Karaganda University “Law Series”, 2023)
The goal of the study is to analyze the problematic aspects of ensuring the protection of personal data when using EDS to sign smart contracts and conclude such contracts related to the implementation of electronic commerce based on blockchain technology. The article discusses the trends and problems observed today in the development of electronic commerce in the republic, related to the state registration of electronic contracts and the protection of personal data. As research methods, along with general methods of scientific research, such as analysis, synthesis, historical, formal and logical, private methods, such as comparative legal research, modeling, were also used. For example, a model of real estate registration services has been developed, ensuring the protection of personal data when using EDS using blockchain technology. In the course of the study, the following results were achieved: the mechanism of blockchain technology was studied and objective difficulties of legal regulation of this sphere of public relations were identified; analyzed the main regulatory legal acts of the Republic of Kazakhstan regulating the execution and execution of transactions in electronic form; studied foreign experience in the use of blockchain technology in the registration of real estate; the legal regulation of digital technologies in Kazakhstan is analyzed and the concept of a smart contract is defined; the features of ensuring the execution of smart contracts are studied; the main problematic aspects of ensuring the protection of personal data when using EDS are studied. In conclusion of the article, we propose to make additions and amendments to the legislation for the purpose of legal regulation of these processes, including the law “On State Registration of rights to immovable property”.